Rancang Bangun Aplikasi Customer Relantionship Management (CRM) Dengan Metode Double Exponential Smoothing Pada CV. Mulia Sejahtera - Putu Ayu Lestari; I Gede Putu Krisna Juliharta; Ni Made Estiyanti (Primakara University, 2019)
CV. Mulia Sejahtera is one of the companies that pay attention to the customer satisfaction. In accordance with the company tagline which is